Lifestyle wellness coaching - Gavin, James 1942-; Mcbrearty, Madeleine 1948- (Champaign, IL Human Kinetics, 2019)
Lifestyles have changed dramatically over the past quarter century. Along with these changes come exciting opportunities, including new career paths in the professional domain of health and wellness coaching. Centered on an evidence-based process for guiding change, Lifestyle Wellness Coaching, Third Edition, offers a systematic approach to helping clients achieve enduring changes in their personal health and wellness behaviors through a supportive and forward-moving coaching relationship. Lifestyle Wellness Coaching has been thoroughly revised and updated to keep pace with the rapidly evolving field of wellness coaching. It is complemented by discussions, case studies, reflective opportunities, and practical aids and engages readers through multiple approaches to learning: The reader is encouraged to gauge comprehension and application of the content by reflecting on personal experiences within the context of coaching; Sample dialogues offer real-world examples of coaching situations and strategies; The International Coach Federation's 11 core competencies are thoroughly examined to prepare readers for certification in the profession of coaching. Lifestyle Wellness Coaching examines real coaching conversations to assess key considerations, such as the types of questions to ask, how to provide feedback effectively, and how to facilitate action planning. The text presents communication strategies to motivate, guide, inform, and support clients' processes toward personal change with a holistic approach. It addresses boundaries of care and advice appropriate to coaching relationships. Other issues explored include developing a trusting relationship, creating goals that are aligned with coaching processes, unblocking clients' energy and discovering resources for change, and generating forward movement through the skillful use of the International Coach Federation's 11 core competencies. Lifestyle Wellness Coaching introduces readers to models that clearly identify clients' progress through the stages of change. First, the text explores the popular transtheoretical model (TTM) of health-related behavior change and its delineation of six stages of clients' readiness to change. The discussion of TTM includes strategies appropriate to clients in various stages of readiness to change. The text also presents the learning-through-change model (LCM), revealing the deep layers beneath each phase of client movement toward change. Readers are offered a map for coaching clients toward goal achievement. The authors' unique flow model of coaching illustrates how professional coaches can help clients navigate the sometimes turbulent events of a person's life in order to change habitual patterns of behavior. Lifestyle Wellness Coaching, Third Edition, is the definitive resource for those seeking to embrace wellness coaching and propel clients to healthy, effective change.
Chapter 1. Introducing Wellness Coaching -- Chapter 2. Background and Core Ingredients of Coaching -- Chapter 3. Paths of Change -- Chapter 4. Coaching Models -- Chapter 5. Setting the Foundation for Effective Coaching -- Chapter 6. Cocreating the Coaching Relationship -- Chapter 7. The Magic of Listening -- Chapter 8. The Power of Questioning -- Chapter 9. Direct Communication -- Chapter 10. Awareness and Action -- Chapter 11. Goal-Focused Coaching -- Chapter 12. Coaching as a Path of Change -- Appendix A. TTM Decisional Balance: Pros and Cons of Behavior Change -- Appendix B. Sample Lifestyle Wellness Coaching Agreement -- Appendix C. ICF Code of Ethics.
Includes bibliographical references
Online resource; description from publisher's metadata and print version record (viewed on 4 February 2020).
Keywords: Health promotion; Lifestyles; Personal coaching; Physical fitness